12 let laparoskopskih holecistektomij in analiza zgodnjih zapletov - Mušič, Mark (Endoskopska revija, 2005)
Background. From December 1992 to the end of 2004, 1979 laparoscopic cholecystectomies were done at the Surgical Department of the Novo mesto General Hospital. The proportion of laparoscopic cholecystectomies, which had been low until 1997, has increased over the past two years to reach 82 per cent of all biliary operations. In 2004, 5.4 per cent of conversions were recorded. The paper analyses early complications associated with laparoscopic cholecystectomies performed in this institution. In addition to statistical analysis and comparison of results, the paper investigates the causes and consequences of early complications, particularly of iatrogenic biliary injuries. Patients and methods. Seven early complications were documented during a period of 12 years. Two common bile duct injuries, categorized as type E1 according to the Strasberg classification, were identified intraoperatively and managed by accomplishing anastomosis of the common bile duct and by inserting a T-tube. Three patients developed bleeding and had to be reoperated on the same day. In two cases, the laparoscopic approach had to be converted to an open procedure to allow for blood clot removal. In one case, revision of a haemotoma in the postoperative wound was required after the insertion of a supraumbilical trocar. A conventional approach was used in two cases with improperly laced metal clamps. In one patient, the cystic duct clamp was found to be too short and had to be replaced by two larger ones. In another case, compression of the common bile duct by a clamp was suspected at ERCP; the clamp was removed and the cystic duct was ligated in the classical manner. (Abstract trunacted at 2000 characters)
Keywords: Cholecystectomy, Laparoscopic; Holecistoktemija laparoskopska; Treatment Outcome; Zdravljenje, izid; žolčnik; kirurško zdravljenje; laparoskopska kirurgija; zapleti; poškodbe